Sistem Informasi Persediaan dan Mutasi Barang Berbasis Web (Studi Kasus: PT Chitose Cengineering Indonesia) - Aditrie Rachman Alamna; Fahmi Abdullah; Novita Anggraini (CV. Multi Kreasi Media, 2025)
At PT. Chitose Cengineering Indonesia, the warehouse team manages a lot of inventory data daily. However, the existing manual system causes difficulties in tracking item information, data duplication, and frequent stock data loss. To address these problems, a web-based system was developed using UML, PHP, and MySQL to improve inventory data management.